On a functional equation related to some entropies in information theory. (3rd April 2018) - Singh, Dhiraj Kumar; Dass, Pranav
Abstract: The general solutions of the functional equation in which f, g, h are real-valued mappings each with domain I = [0, 1]; ( p 1,  … , pn ) ∈ Г n, ( q 1,  … , qm ) ∈ Г m ; n ≥ 3, m ≥ 3 being fixed integers; α > 0, α ≠ 1, α ∈ ℝ; have been obtained. Some of the solutions are related to entropies of degree α ; entropies of degree ( α, β ); and to Gini-Simpson index.